Enzymic Milk Clotting Activities of Metalloproteinase Kistomin - Jaya Vejayan, Palliah; Amira Alia, Zulkifli; Rupbansraaj, Bathmanathan; Halijah, Ibrahim (Science Alert, 2020)
Background and Objectives: The dairy industry is in constant search for newer milk clotting coagulants to substitute rennet due to its growing demands and controversies such as; its origin from young slaughtered animals. Kistomin (EC:3.4.24) is a protease long identified on its role to cleave platelet and fibrinogen. In this study, kistomin discovered to function as a milk coagulant and investigated for its milk clotting activities. Materials and Methods: Kistomin investigated by measuring its Milk Clotting Activity (MCA) and Proteolytic Activity (PA), optimum conditions of pH, temperature, concentrations of enzyme and calcium chloride, exposures to various chelating agents and cofactor ions. Results: The MCA of kistomin was 810.44 (SU mLG1 ) and the PA was 1.39 (U mLG1 ), resulted in a ratio of MCA/PA value of 583. The coagulating activity of kistomin on milk was the highest at 0.76 mg mLG1 enzyme concentration, 8% (w/v) of CaCl2 concentration, the temperature of 48EC and stable over a wide range of pH 5-7 with activity peaking at pH6.5. The protease completely inhibited by EDTA and 1,10 phenanthroline verifying to be a metalloprotease. The addition of Ba2+, Mn2+ and Ca2+ significantly increased the enzyme activity but inhibited by Hg2+, Pb2+ and Fe2+ ions. Kistomin promoted extensive hydrolysis of κ-casein and low level of β-casein cleavage. Conclusion: This concluded that kistomin can be used as a milk clotting candidate for the dairy industry.